Contextual Determinants of Stunting in Indonesia: A Systematic Review of Nutritional Interventions and Antenatal Care - Setiawan Limijadi, Edward Kurnia; Devi, Katrin Setio (International Journal of Child Health and Nutrition, 2025)
Background: Stunting is a significant global health issue, especially in Indonesia, where long-term malnutrition adversely affects children's growth and development, with prevalence rates still exceeding the WHO's recommended threshold. This study examines the contextual factors that influence the effectiveness of nutritional interventions and antenatal care (ANC) in combating stunting in Indonesia. Methods: A systematic review was conducted by the PRISMA guidelines. A comprehensive search across five major academic databases (Google Scholar, PubMed, ScienceDirect, Embase, and ProQuest) identified 3,690 articles. After a rigorous screening process, 13 studies published between 2019 and 2023 were included in the analysis, focusing on key contextual factors that impact stunting interventions in Indonesia. The quality appraisal utilized Joanna Briggs Institute checklists for analytical cross-sectional studies, cohort studies, quasi-experimental studies, qualitative research, systematic reviews, case reports, and text and opinion papers, each matched to the respective study design. Findings: The review identified four critical contextual factors shaping stunting interventions: (1) socioeconomic status, particularly household income and education, which significantly influence access to healthcare and nutrition; (2) cultural beliefs, including food taboos and misconceptions, which hinder optimal nutritional practices; (3) geographical disparities, with rural populations experiencing higher stunting rates due to limited access to healthcare and resources; and (4) government policies, highlighting the importance of strong political commitment, multisectoral collaboration, and localized programs. Conclusion: Nutritional interventions and ANC are more effective in reducing stunting among Indonesian children when tailored to local socioeconomic, cultural, and geographical contexts. These findings highlight the need for targeted, context-specific strategies to improve child growth outcomes in vulnerable populations.